Over seas of memory : a novel - Ferrier, Michaël (University of Nebraska Press, 2019)
"In this novel based loosely on the author's life, the narrator traces the colorful story of his Mauritius-born grandfather, Maxime, who abruptly boarded a boat bound for Madagascar in 1922 and never returned. Ferrier narrates a tale of discovery, weaving personal stories with the island's history"--